Influence of the external magnetic field on the cylindrical electron bunch injected into plasma - Shcherbinin, M.A.; Anisimov, I.O. (Вопросы атомной науки и техники, 2014)
Dynamics of the initially cylindrical electron bunch injected into plasma along the external magnetic field was studied via PIC simulation. Time evolution of the spatial distributions of electric field, magnetic field and bunch electron density is analyzed. The influence of the external magnetic field on the bunch shape and wake field excitation is treated. The correlation between azimuthal magnetic field distribution and wake field shape is discussed.